Press freedom in Malaysia and its effect on political transparency / Ezzah Ruzaini Mohd Radzi … [et al.] - Mohd Radzi, Ezzah Ruzaini; Hani Eshak, Ida Yuszrin; Azhar, Nur Dalilah; Awang, Yasmin Adilah (2014)
The purpose of this research is to identify whether there is freedom of press in Malaysia and what laws can be adopted in foreign countries to better facilitate press freedom in Malaysia. The design that was used in this research is an Analytical study, where qualitative doctrinal method is applied using the traditional approach where research is based on findings in relevant books, journal articles, newspaper articles, legal comments, legislative enactment and previous research conducted were used in answering the research problems. This study focuses on the laws in Malaysia that curb freedom of speech and compare these laws to those of other model countries. Case laws are used as an examples or evidence to show the lack of freedom of press in Malaysia.